The performance of determinants of unit trust fund in Malaysia / Nurul Fatiha Ikhmah Idris - Idris, Nurul Fatiha Ikhmah (2017)
The unit trust is an investment scheme, where money can be pooled from many individuals and channels. The unit trust industry is one of the fastest developing in the financial sector. Since this industry is developing too fast, it makes the investor and interested bodies willing to know more about this investment. This study is to identify the performance determinants of the unit trust fund in Malaysia. In this study, data were collected from secondary data and involved 10 management companies of unit trust with 49 types of unit trust fund in Malaysia. The financial data are gather from company’s annual report. This study covers five years period from 2012 to 2016. In the study, data were generated by using Statistical and Data Analysis software (STATA). This study will identify whether three factors have positive relationship to the performance of unit trust. The study shows a significant positive relationship of two factors which is diversification and expense ratios to the performance of unit trust. whilst, the other factor which is fund size has negative relationship to the performance of unit trust. The result indicates the investor have to make better decision to maximize their fund performance.